Rubikon [videorecording (DVD)] - Richter, Julia Franz; Blagden, George, 1989-; Ivanir, Mark; Monu, Nicholas, 1965-; Lind, Jessica (IFC Midnight, 2022)
Following a catastrophe on Earth, the planet is covered in a toxic fog. The crew in the space station must decide whether to risk their lives to get home and search for survivors, or stay safe in the station's algae symbiosis system.